Market-function asset purchases - Darrell Duffie; Frank Keane (Federal Reserve Bank of New York, 2023)
This paper investigates the goals, costs, and benefits of official-sector purchases of government securities for the purpose of restoring market functionality. We explore the design of market-function purchase programs, including their communication, triggers, operational protocols, exit, and wind-down strategies. We further discuss whether, under some circumstances, fiscal buybacks might be a useful alternative or complement to central-bank market-function purchase programs, and how these buybacks could be funded. The use of fiscal buybacks to support market functionality can be aligned with the fiscal authority's goal of minimizing the government's interest expense and can reduce challenges that can be faced by a central bank when asset purchases are not naturally congruent with monetary policy. Depending on the setting and circumstances, fiscal buybacks can also mitigate perceptions of risks to the central bank's independence.
Keywords: D53; E52; E58; E44; E61; 330; government securities; financial stability; bond markets; central banking; debt management